Recent research in mobile computing: A review and taxonomy of HCI issues - Mohamedally, Dean; Zaphiris, Panayiotis; Petrie, Helen (My University, 2003)
This paper presents an overview of Human Computer Interaction issues in mobile systems based on publications from the past five years (1998-2002). The research is summarized in two taxonomies, one by research topic and one by design lifecycle stage. These taxonomies highlight those areas where most research has been focussed and those areas currently lacking research.